PEMANFAATAN TIKTOK SEBAGAI MEDIA EDUKASI DI MASA PANDEMI COVID-19 - Chotijah Fanaqi; Ismira R Febrina; Resty Mustika Pratiwi; Gymnastiar Gymnastiar (Universitas Garut, 2022)
Abstract This research is motivated by the increasing use of TikTok social media during the covid 19 period. The use of TikTok social media is inseparable from the purpose of its users as an entertainment medium during the covid 19 pandemic, it also has specific goals such as an educational media that helps users get information about education, teaching, tips and tricks, and so on. This study aims to explain the use of TikTok social media for educational media during the COVID-19 pandemic. This research method uses descriptive qualitative with data collection techniques by interviews, observations, and literature studies that are relevant to the research discussion. Ten informants were selected based on the criteria as content creators and connoisseurs of educational content on TikTok during the pandemic of COVID-19 who came from various professions and of various ages including students, teachers, political observers, housewives, health workers, and so on. The results of the study revealed that the use of the Tiktok application was quite effective during the pandemic of Covid-19, where most community activities were carried out on a limited basis as an effort to prevent Covid-19 transmission. Besides being useful as an entertainment medium to increase immunity (mood booster) for its users, TikTok is also used as an educational medium to get information and knowledge about certain things that are the goals of its users. Some of the educational benefits include providing tutorials on learning English, procedures for completing a final project or thesis, practical tutorials using Microsoft word, cooking tutorials, make-up tutorials, complementary feeding tutorials for mothers who have just had toddlers, and knowledge about counseling. In addition to educational benefits, the use of TikTok also has a vulnerability in the spread of hoax news. So it is recommended for users to report accounts that are considered irresponsible as an effort to break up hoax information so that it does not spread more widely. Keywords: TikTok; educational media; pandemic of covid 19 AbstrakPenelitian ini dilatarbelakangi oleh penggunaan media social TikTok yang meningkat di masa covid 19. Penggunaan media social TikTok disamping tidak terlepas dari tujuan para penggunanya sebagai media hiburan di masa pandemic covid 19, juga memiliki tujuan spesifik seperti sebagai media edukasi yang membantu penggunanya mendapatkan informasi seputar Pendidikan, pengajaran, tips dan trik, dan lain sebagainya. Penelitian ini bertujuan untuk menjelaskan pemanfaatan media social TikTok untuk media edukasi di masa pandemic covid 19. Metode penelitian ini menggunakan kualitatif deskriptif melalui teknik pengumpulan data berupa teknik wawancara, observasi, dan studi pustaka terkait persoalan yang relevan dengan pembahasan penelitian. Sepuluh informan dipilih berdasarkan kriteria sebagai konten creator dan penikmat konten edukasi di TikTok selama masa pandemic covid 19 yang berasal dari berbagai profesi dan berbagai usia meliputi mahasiswa, guru, pengamat politik, ibu rumah tangga, tenaga kesehatan, dan lain sebagainya. Hasil penelitian menjelaskan bahwa pemanfaatan aplikasi Tiktok cukup efektif di masa pandemi Covid-19 yang sebagian besar aktivitas masyarakat dilakukan secara terbatas sebagai upaya pencegahan penularan Covid-19. Selain bermanfaat sebagai media hiburan untuk meningkatkan imun (mood booster) bagi para penggunanya, TikTok juga dimanfaatkan sebagai media edukasi untuk mendapatkan informasi dan pengetahuan mengenai hal-hal tertentu yang menjadi tujuan para penggunanya. Beberapa manfaat edukasi tersebut diantaranya memberikan tutorial mengenai belajar Bahasa Inggris, Tata cara penyelesaian tugas akhir atau skripsi, Tutorial praktek menggunakan Microsoft word, Tutorial Memasak, Tutorial Make Up, Tutorial MPASI bagi Ibu-ibu yang baru memiliki balita, dan pengetahuan mengenai konseling. Selain manfaat edukasi, penggunaan TikTok juga memiliki kerentanan dalam penyebaran berita hoax. Maka disarankan bagi pengguna untuk mereport akun yang dianggap tidak bertanggunjawab tersebut sebagai upaya memutus informasi hoax agar tidak tersebar lebih luas. Kata-kata kunci: TikTok; media edukasi;pPandemi covid 19